Propagação in vitro de Moringa oleifera L. - Cysne, Júnior Régis Batista (2006)
Moringa Moringa oleifera Lam is a tree plant belonging to the family Moringaceae widely used for the chemical properties its seeds. In this work, we attempted to develop a basic protocol for the micropropagation of the plant. Shoot apexes originating from in vitro germinated seedlings on Murashige and Skoog (MS) medium were used as primary explants. Adventitious shoots obtained from field growing trees were also isolated and inoculated on Wood Plant Medium (WPM) for the same purpose. Subjecting the seeds to various regimes and sequences of surface sterilization using sodium hypochlorite (NaOCl) showed that the best regime is the use of 0.25% NaOCl for 10 minutes. In an attempt to micropropagate Moringa, excised adventitious shoots were cultured on MS medium for 12 days, following which they were transferred to MS medium supplemented with varying concentrations (0.0,0.05,1.25 and 6.25uM) of 6-Benzylaminopurine (BAP). Explants subjected to the medium containing 1.25uM BAP demonstrated the highest rate of multiplication of 89%. In order to optimize the regeneration of plants from the primary explants, they were subjected to combinations of BAP and Indol-3-butyric acid at various concentrations. Although the highest rate of regeneration and shoot elongation was obtained when equimolar concentrations of BAP and IBA of 0.25uM was supplemented in an MS medium, there was a sharp decrease in the rate of multiplication from 89.5% to 50.8% when the shoots were sub cultured onto the same medium after 28 days. Subjecting shoot apexes obtained from field growing plants to WPM and MS based medium formulations, it was discovered that WPM promoted better proliferation of the explant compared to all other medium. Using WPM supplemented with different concentrations of BAP (0.0,0.05,0.25,1.25), the medium containing 6.25uM BAP was found to result in formation of callus followed by shoot formation. Transferring the proliferating shoots to a medium containing 0.25uM BAP led to their development without formation of adventitious shoots.